Estudo da fertilidade em ratas com artrite: efeito modulatorio de drogas que inibem a ciclooxigenase e o fator de necrose tumoral - Silva, José Clielder Rebouças da (2000)
This study examined the role of chronic inflammatory disease in reproduction using adjuvant-induced arthritis in rat as an animal model that simulates human rheumatoid arthritis. Arthritis was induced by subplantar injection of Freund’s Complete Adjuvant (FCA) into the right hind paw of Wistar female rats. The time- course of inflammatory reaction as measured by plethysmography of the incremenr in contralateral paw volume (secondary reaction), body weight changes, haematological and biochemical alterations, leveis of serum cytokines EL-1(3 and TNFa and the histopatological changes in tibio-tarsal joint, ovary and uterus were documented. Besides, we verified the differences, if any, between the arthritic and non-arthritic rats on the pattem of oestrus cycle, fecundation and pregnancy outcome. Furthermore, the treatment effects of more selective ciclooxygenase 1 (COX-1) and ciclooxygenase 2 (COX-2) inhibitors, indomethacin and nabumetone, respectively, and pentoxifylline, a compound that inhibits TNFa production, were analysed on joint inflammation and serum cytokines IL-ip and TNFa leveis. In order to know whether pregnancy has some influence on the development of arthritis, adjuvant arthritic female rats were mated with proven fertile males between day 10 and 15 post-FCA injection and the pregnancy was confirmed by examination of vaginal smears. It was also investigated the possible anti- arthritic efficacy of a standardized human placental extract administrated between day 10 and 20 after FCA. In arthritic rats, the serum IL-ip and TNFa leveis were greatly elevated on the very first day i.e. 5 h after FCA, and thereupon a progressive decrease in IL-ip but not TNFa was observed until day 30. The secondary arthritic reaction began to increase on day 14 and attained its peak on day 21 post-adjuvant injection. The peak arthritic lesion was significantly less in rats that received cyclooxygenase and TNFa inhibitors. When serum cytokine leveis were analysed on day 20 post-adjuvant injection, rats treated with pentoxifylline or its association with nabumetone but not nabumetone alone showed significantly lowered leveis of serum TNFa. Unlike TNFa, serum EL-1(3 did not vary significantly. The drugs nabumetone and pentoxifylline although produced differential effects on serum cytokine leveis, they showed equal efficacy in atenuating the progression of FCA-induced arthritis. It implies that serum cytokine leveis do not accurately reflect the treatment efficacy. The arthritic rats besides showing histologic evidences of joint inflammation, presented reduced number of growing follicles in ovary and infiltration of inflammatory cells predominantly eosinophils and plasma cells in uterus. Besides, arthritic rats showed body weight loss, prolongation of oestrus cycle, decreased number of uterine ovoimplantations and low fertility. Indomethacin (2 mg/kg,p.o.), nabumetone (20 mg/kg,p.o.) or pentoxifylline (20 mg/kg,p.o.) treatments, however, failed to reverse the reduced fertility seen in arthritic rats. The peak paw inflammatory response was significantly less in the rats on pregnancy and in those that received placental extract (400 mg/kg, i.p.) between days 10 to 20 of adjuvant arthritis. Furthermore, the placental extract was the only treatment that reversed the low body weight gain seen in arthritic rats. In conclusion, this study shows that adjuvant arthritis affects negatively the reproduction in the rat and suggests that pregnancy has a modulatory influence on arthritis probably involving placental-related factors, whose identity remains to be studied. The potential use of COX inhibitors and INF antagonists to suppress arthritis although appear rewarding, do not seem to alleviate the arthritis associated low fertility.